ВДОСКОНАЛЕНА МАТЕМАТИЧНА МОДЕЛЬ ТРИОБМОТКОВОЇ АСИНХРОННОЇ МАШИНИ - Мазуренко, Л.І.; Василів, K.M.; Джура, О.В. (Інститут електродинаміки НАН України, Київ, 2023)
In phase coordinates, a mathematical model of a three-winding asynchronous machine with two windings on the stator as a structural element of electric drives and asynchronous generators with inverter and inverter-capacitor excitation for autonomous electric power plants, oriented to explicit methods of numerical integration of the system of differential equations, has been developed. The model takes into account the displacement angle between two stator windings in the range of 360º and other important factors affecting the course of electromagnetic processes occurring in the machine. On the basis of the mathematical model, a program code was developed as a means of computer verification of machine operation modes. The results of computer study performed with the help of the code confirm the suitability of the mathematical model of a three-winding asynchronous machine to take into account the influence of the displacement angle between the stator windings and their simultaneous and single power supply during the operation of the machine in motor mode. References 11, figures 10.